2018
DOI: 10.1590/0074-02760180171
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin exerts anti-inflammatory and vasoprotective effects through amelioration of NFAT-dependent endothelin-1 production in mice with acute Chagas cardiomyopathy

Abstract: BACKGROUND The anti-inflammatory and cardioprotective properties of curcumin (Cur), a natural polyphenolic flavonoid isolated from the rhizomes of Curcuma longa, are increasingly considered to have beneficial effects on the progression of Chagas heart disease, caused by the protozoan parasite Trypanosoma cruzi.OBJECTIVE To evaluate the effects of oral therapy with Cur on T. cruzi-mediated cardiovasculopathy in acutely infected mice and analyse the in vitro response of parasite-infected human microvascular endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…Vasconcelo et al, 2017N,N dimethylsphingosin (Sphingosine kinase inhibitor)C57BL/6 miceReduction of cardiac inflammation, fibrosis and galectin-3 expression, modulation of inflammatory mediators such as IFNγ and TNFα, improvement in exercise capacity, but without improving cardiac electrical disturbances.Montenote et al, 2017 M. nigra (Phytotherapeutic compound)Swiss miceDecreased parasitemia, and may be the subject of further research for a greater analysis of the mechanisms of action and bioavailability.Horta et al, 2017Carvedilol (Adrenergic Blocker)C57BL/6 miceFor this experimental model, carvedilol therapy was not able to alter levels of circulating parasites, but modulates the pattern of mediators of CCL2 and IL-10 when the VL10 strain of T. cruzi. Reigada et al, 2017Isotretinoin (Antiacne)CHO–K1 cellsIsotretinoin inhibited polyamine transport, also showed strong inhibition of the explanted trypomastigote of infected cells but being significantly less effective at the epimastigote stage.Hernández et al (2018)Curcumin (cholagogue, anti-inflammatory)Human microvascular endothelial cells, C57BL/6 miceReduced inflammatory cell infiltration without lowering parasitemia.Ferreira et al (2018)Sertraline (Antidepressant)In silico studies, Balb/c mice E fficacy against intracellular amastigotes and bloodstream trypomastigotes, with low cytotoxicity to mammalian cellsFracasso et al, 2018Resveratrol (antioxidant/cardioprotective)Swiss miceCan be use for the treatment of neuroinflammation or neuroprotection during Chagas disease, improving gliogenesis and restoring neural migration.Simões-Silva et al (2019)Imatinib (Antineoplastic Agent Immunological Agent)Mouse fibroblastsThe drug was moderately active against the parasite, with low selectivity indexND* not determined.…”
Section: Repositioning Of Therapeutic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasconcelo et al, 2017N,N dimethylsphingosin (Sphingosine kinase inhibitor)C57BL/6 miceReduction of cardiac inflammation, fibrosis and galectin-3 expression, modulation of inflammatory mediators such as IFNγ and TNFα, improvement in exercise capacity, but without improving cardiac electrical disturbances.Montenote et al, 2017 M. nigra (Phytotherapeutic compound)Swiss miceDecreased parasitemia, and may be the subject of further research for a greater analysis of the mechanisms of action and bioavailability.Horta et al, 2017Carvedilol (Adrenergic Blocker)C57BL/6 miceFor this experimental model, carvedilol therapy was not able to alter levels of circulating parasites, but modulates the pattern of mediators of CCL2 and IL-10 when the VL10 strain of T. cruzi. Reigada et al, 2017Isotretinoin (Antiacne)CHO–K1 cellsIsotretinoin inhibited polyamine transport, also showed strong inhibition of the explanted trypomastigote of infected cells but being significantly less effective at the epimastigote stage.Hernández et al (2018)Curcumin (cholagogue, anti-inflammatory)Human microvascular endothelial cells, C57BL/6 miceReduced inflammatory cell infiltration without lowering parasitemia.Ferreira et al (2018)Sertraline (Antidepressant)In silico studies, Balb/c mice E fficacy against intracellular amastigotes and bloodstream trypomastigotes, with low cytotoxicity to mammalian cellsFracasso et al, 2018Resveratrol (antioxidant/cardioprotective)Swiss miceCan be use for the treatment of neuroinflammation or neuroprotection during Chagas disease, improving gliogenesis and restoring neural migration.Simões-Silva et al (2019)Imatinib (Antineoplastic Agent Immunological Agent)Mouse fibroblastsThe drug was moderately active against the parasite, with low selectivity indexND* not determined.…”
Section: Repositioning Of Therapeutic Drugsmentioning
confidence: 99%
“…Furthermore, resveratrol acts as a neuroprotector during CD, improving gliogenesis and neural migration (Fracasso et al, 2019). Curcumin, a herbal supplement and a natural food coloring extracted from ginger, is a natural phenol that failed in reducing parasitemia, although lowering inflammatory leukocyte infiltration (Hernández et al, 2018).…”
Section: Repositioning Of Therapeutic Drugsmentioning
confidence: 99%
“…Furthermore, the in vitro study showed that curcumin decreases the release of the vasoactive peptide, reduces [Ca 2+ ] i response, and prevents parasite-triggered NFATc1 nuclear translocation, leading to the cytoplasmic accumulation of NFATc1 protein ( Figure 1 ). This suggests that curcumin possesses cardioprotective activity and may abolish the [Ca 2+ ] i -associated activation of the NFATc1 isoform in vascular endothelial cells infected by Trypanosoma cruzi [ 24 ].…”
Section: Cardioprotective Activity Of Polyphenolsmentioning
confidence: 99%
“…There is much controversy about the effect of H 2 S, leptin and curcumin in inflammatory condi-tions. Some studies have shown that they may have pro-inflammatory effects (Ang et al 2013;Singh et al 2014; Pham and Mathis 2017), while, others have proved the anti-inflammatory effects of them (Qi et al 2017;Ali et al 2018;Hernandez et al 2018).…”
Section: Discussionmentioning
confidence: 99%